Sommes binomiales (3/3)

Exercice 1.
Avec {n\in\mathbb{N}^*} et {0\le p\le n}, montrer que {\displaystyle\sum_{k=0}^{p}(-1)^k\displaystyle\binom{n}{k}=(-1)^p\displaystyle\binom{n-1}{p}}.
Cliquer ici pour voir (ou cacher) le corrigé

Exercice 2.
Pour tout {n} de {\mathbb{N}}, montrer que {\displaystyle\sum_{k=0}^{2n}(-1)^k\displaystyle\binom{2n}{k}^2=(-1)^n\displaystyle\binom{2n}{n}}.
Cliquer ici pour voir (ou cacher) le corrigé

Exercice 3.
Montrer que la suite {n\mapsto u_n=\displaystyle\sum_{k=0}^{[n/2]}(-1)^k\displaystyle\binom{n-k}{k}} est périodique.
Cliquer ici pour voir (ou cacher) le corrigé

Exercice 4.
Soient {m,n} dans {\mathbb{N}}, avec {0\le m\le n}.
Montrer que, pour tout {p\in\mathbb{N}} : {\displaystyle\binom{n}{p}=\displaystyle\sum_{k=0}^{m}\displaystyle\binom{m}{k}\displaystyle\binom{n-m}{p-k}}.
Remarque : par convention, {\displaystyle\binom{n}{p}=0} si {p\lt 0} ou si {p>n}.
Cliquer ici pour voir (ou cacher) le corrigé